Choices and Patterns of English Names among Taiwanese Students. (December 2015) - Chen, Lindsey N. H.
Abstract : The English names of 248 students studying at a Taiwan university were examined to study the choices and patterns of English names. Consistent with previous findings, female names were significantly more likely than male names to end in one of three vowels, a, e, or i, while male names were significantly more likely to end in consonants. Monosyllabic English names were equally common among males and females, in contrast to previous findings that one-syllable names are significantly more common among males. Finally, homophonization was a common phenomenon among male and female names. The findings of this study indicate that the choice of an English name is partly motivated by a sense of identity preservation.